Sistema de medición de la calidad de la educación de la calidad de la educación básica: una propuesta - Filp, Johanna; Espínola, Viola; Latorre, Marcela; Cariola, Leonor; Santibañez, Erika; Cuadra, Gustavo; Rojas, Alfredo; Zúñiga, Luiz; García-Huldobro, Juan Eduardo (Estudos em Avaliação Educacional, 1990)